Anthropogenic aerosols prolong fog lifetime in China - Jiannong Quan; Yangang Liu; Xingcan Jia; Lin Liu; Youjun Dou; Jinyuan Xin; John H Seinfeld (Environmental Research Letters, 2021)
Investigation of aerosol effects on fog with long-term measurements has generally focused on fog occurrence frequency and intensity; here we examine the effects on fog lifetime, fog formation, and fog dissipation. From analysis of 52 years (1960–2011) of data collected at 404 stations in China, it is found that fog lifetime exhibits a clear increasing trend with time, and the increased lifetime is mainly attributable to delayed fog dissipation. Increased aerosol levels and global warming affect fog lifetime in opposite ways; increased aerosol levels serve to prolong fog lifetime by primarily delaying fog dissipation, whereas warming decreases fog lifetime by primarily delaying fog formation. The overall aerosol effect on fog lifetime in China is shown to predominate, especially in the highly polluted region of Eastern China. The observational findings are confirmed by a suite of WRF-Chem simulations that reveal the influences of both increased aerosol levels and temperatures through a complex chain of interactions among microphysical, dynamical, thermodynamic, and radiative processes.